Mesoporous Polydopamine Loaded Pirfenidone Target to Fibroblast Activation Protein for Pulmonary Fibrosis Therapy - Fang, Qi; Liu, Shaoyu; Cui, Jiangyu; Zhao, Ruiyue; Han, Qian; Hou, Peng; Li, Youcai; Lv, Jie; Zhang, Xiaoyao; Luo, Qun; Wang, Xinlu (Frontiers in Bioengineering and Biotechnology, 2022)
Recently, fibroblast activation protein (FAP), an overexpressed transmembrane protein of activated fibroblast in pulmonary fibrosis, has been considered as the new target for diagnosing and treating pulmonary fibrosis. In this work, mesoporous polydopamine (MPDA), which is facile prepared and easily modified, is developed as a carrier to load antifibrosis drug pirfenidone (PFD) and linking FAP inhibitor (FAPI) to realize lesion targeted drug delivery for pulmonary fibrosis therapy. We have found that PFD@MPDA-FAPI is well biocompatible and with good properties of antifibrosis when ICG labels MPDA-FAPI, the accumulation of the nanodrug at fibrosis lung in vivo can be observed by NIR imaging, the antifibrosis properties of PFD@MPDA-FAPI in vivo was also better than pure PFD and PFD@MPDA, therefore the easily produced and biocompatible nanodrug PFD@MPDA-FAPI developed in this study is promising for further clinic translations in pulmonary fibrosis antifibrosis therapy.